The determination of efficiency of a special obstacle course for training of cadets and rescuers of Public Service of Ukraine on emergency situations - Olexandr Baybak; Irina Baybak; Vladislav Buhors'kyy; Svetlana Pyatisotskaya (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to determine directions of the improvement of the educational and training process of cadets and retraining of rescuers of Public Service of Ukraine on emergency situations (PSES) for carrying out the search-rescue works in highlands. Material & Methods: the contingent - cadets (25), rescuers (25) and officers (25) of Public Services of Ukraine on emergency situations took part in the research. The following methods are used for the solution of objectives: the theoretical analysis and generalization of scientific and methodical literature, pedagogical methods of research (poll and questioning). Results: the main requirements to a special obstacle course were defined on the basis of studying and analysis of biographical particulars with the purpose of the improvement of rescuers of PSES for carrying out the search-rescue works (SRW) during the emergency situations (ES) of a natural character. Conclusions: the need of modeling of weather conditions on a special obstacle course is defined for the purpose of the improvement of the level of preparedness of staff of the search-rescue groups in highlands.